Perikatan Bersyarat dalam Hukum Perdata Indonesia Implikasi dari Putusan Mahkamah Agung terhadap Praktik Bisnis - Dwikornida, Dwikornida; Islam, Syaifuddin (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
Conditional obligations are a fundamental concept in Indonesian civil law that provide flexibility in business transactions. Regulated in Article 1253 of the Indonesian Civil Code, these obligations allow the execution of a contract to be dependent on certain conditions that have not yet occurred. In business practice, conditional obligations are often applied in sales and purchase agreements, international business contracts, and transactions involving government regulations. One important aspect of their implementation is legal certainty, which is emphasized in Supreme Court Decision No. 218 PK/Pdt/2015, which states that agreements that are dependent on government approval cannot be executed before obtaining such approval. An analysis of this decision highlights the important legal implications of conditional obligations, both in ensuring legal protection and managing uncertainty in business agreements. Comparative studies with international legal systems, such as European civil law and common law, reveal that conditional obligations are widely recognized as a universal legal instrument in business contracts. Therefore, a thorough understanding of conditional obligations is essential for business practitioners and legal professionals to ensure effective agreements that minimize risk and comply with applicable legal regulations.